Recent Development-2 of CADTEL Software: The Optimum Conditions of Scherzer Imaging in the Electron Magnetic Lenses - Hasan, Hussain S.; Obaid, Sura Allawi; Erhayief, Muhssen Salbookh (Iraqi Journal of Science, 2022)
CADTEL software was developed to provide the simplest and most versatile computing resource that a wide range of skilled researchers and designers can use. In this paper, a development on this program, relying on sixteen mathematical models, produced a new version of CADTEL software package which focuses on the optimum conditions of Scherzer imaging for round electron magnetic lenses.. These models depend on synthesis procedure which is mainly designed to work with the inverse design problem, and represent the axial magnetic flux density of desirable electron magnetic lens which can be proposed or selected , using the four (zero, low, high, infinite) magnification states. The program provides the freedom of selecting multiple models and changing its variables (which appear on the home page), in addition to providing facilities for numerous proposed magnetic lens. The objective properties calculated in the program were used to compute and plot the optimum conditions for Scherzer imaging The CADTEL software was written in Visual Basic – 6, in an easy-to-use mode, even for a beginner computer user. The results of the analysis clearly show that there is an excellent equivalent calculation which could be obtained for the same lens from CADTEL software when evaluated with other counterpart software.